Microwave-assisted hydrothermal synthesis and electrochemical studies of α- and h-MoO3 - Zakharova, Galina S.; Schmidt, Christina; Ottmann, Alexander; Mijowska, Ewa; Klingeler, Rüdiger (Journal of solid state electrochemistry, 2018)
Two modifications of molybdenum trioxide with orthorhombic (α-MoO3) and hexagonal (h-MoO3) crystal structure have been synthesized by a microwave-assisted hydrothermal method, facilitated by formic acid. Characterization by means of X-ray diffraction, scanning electron microscopy, specific surface analysis, and Fourier-transform infrared, Raman, and UV-Vis spectroscopy reveals phase-pure crystalline powder samples of hexagonal h-MoO3 microrods and of α-MoO3 nanobelt bundles, respectively. The electrochemical properties of the MoO3 compounds, studied by cyclic voltammetry and galvanostatic cycling vs. Li/Li+, strongly depend on the structure and the applied potential range. In the range of 1.5-3.5 V, Li+-ions can be reversibly intercalated into the α-MoO3 nanobelts. Utilizing the material in this way as intercalation cathode material yields an initial discharge capacity of 295 mA h g−1 at 100 mA g−1 and comparably moderate capacity fading of 25% between cycles 20 and 100. Extending the potential range to 0.01-3.0 V induces the conversion reaction to Mo, which for both modifications yields high initial capacities of around 1500 mA h g−1 but is associated with much stronger capacity fading.